INPB: indústria cervejeira - Gonçalves, Felipe de Mello (2023)
Beer is a fermented beverage that is estimated to have been consumed for more than 8000 years and that still attracts new consumers over the years, with great acceptance in the taste of societies. In Brazil, its history dates back to the mid-1650s, and since then, new recipes have emerged according to the creativity and desire to make beer. The national beer industry is the third largest in the word, just behind the United States and China, which reinforces its popularity and how it moves the country`s economy. From a projection of 23.93 billions liters of beer in the year 2040, the INPB (National Beverage Production Industry) comes up with the project to supply 5% of this amount with Pilsen beers, Pure Malt Lager and IPA (India Pale Ale) also, with the vision of further diversifying the offer of its products in the future. Given the stipulated percentage, the estimated production is 700 million liters for Pilsen, 300 million for Pure Malt Lager and 100 million for IPA. Located in Rio do Sul – SC, the installation values its proximity to the necessary raw materials and the large water supply. In addition, water quality is a fundamental point for INPB processes, and therefore, steps such as ion exchange and ultrafiltration will guarantee an excellent level of this raw material, without attributing unpleasant aromas or flavors to the products.